Whither voluntary communities of co-located patients in Vietnam? Empirical evidence from a 2016 medical survey dataset - Vuong, Quan-Hoang (Indian Journal of Community Health, 2016)
Background: Empirical evidence on quality of life of poor patients falls short for policy-making in Vietnam. Financial burdens and isolation give rise to Vietnamese voluntary co-location clusters where patients seek to rely on each other. These communities, although important, have been under-researched. Increasingly, there are questions about their sustainability. Aim & Objectives: This study aims to identify factors that affect sustainability of such co-location clusters, seeking to measure the community prospect through critical determinants as seen by member patients. An in-depth analysis is expected to yield insights that help shape future policies contributing to improvement of healthcare systems. Material & Method: A dataset containing responses from 336 patients living in four clusters in Hanoi was obtained from a survey during 2015Q4-2016Q1. The processing of data is performed using R 3.2.3, employing baseline category logit models (BCL). Coefficients are estimated to compute empirical probabilities. Results: 1) There is a 50% probability that a patient seeing his/her benefits as unsatisfactory views the community prospect as dim; 2) The more a patient contributes time/effort, the less he/she believes in future growth; 3) There is a 80.8% probability that a patient who makes a significant financial contribution and receives back in-kind benefits predicts no growth. Conclusion: Patients predict community growth when receiving what they need/expect. There exists a kind of “liquidity preference”. Only 14% and 32% make significant financial and labor contributions, respectively. There exists a “risk aversion” attitude, viewing contribution as certain while future benefits to be uncertain.